Red Hat Certified System Administrator complete video course - Vugt, Sander van; Safari eBooks ([Place of publication not identified] : Pearson IT Certification, 2015)
"Red Hat Certified System Administrator (RHCSA) and Red Hat Certified Engineer (RHCE) Complete Video Course Library provides the opportunity to study for both the Red Hat Certified System Administrator (RHCSA) and the Red Hat Certified Engineer (RHCE) exams. This Complete Video Course Library offers more than 21 hours of personal visual instruction from an RHCSA and RHCE certified expert with more than 20 years of practical Linux teaching experience. Through the use of topic-focused instructional videos you will gain an in-depth understanding of the Red Hat Certified Administrator (RHCSA) and Red Hat Certified Engineer (RHCE) exams as well as a deeper understanding of Red Hat Enterprise Linux so you master key foundational principles. Included with the product are practice question exercises, with the instructor walking students through both the scenarios and solutions to give you the extra edge you need to excel on the exam. The course includes 100% coverage of the RHCSA and RHCE exam objectives."--Resource description page.
Title from title screen (viewed September 18, 2015).
Presenter, Sander van Vugt.
Keywords: Linux -- Certification; Electronic data processing personnel -- Certification; Systems engineering; Electronic books